Altered Tryptophan Catabolism in Placentas From Women With Pre-eclampsia. (April 2019) - Keaton, Sarah A; Heilman, Patrick; Bryleva, Elena Y; Madaj, Zachary; Krzyzanowski, Stanislaw; Grit, Jamie; Miller, Emily S; Jälmby, Maya; Kalapotharakos, Grigoros; Racicot, Karen; Fazleabas, Asgerally; Hansson, Stefan R; et al.
Background: The kynurenine pathway enzymes, breaking down tryptophan, are abundant in placental tissue. These metabolites are involved in immunoregulatory mechanisms, although the role of this pathway in pre-eclampsia (PE) has only begun to be characterized. Here, we determined tryptophan and metabolite levels together with the expression of kynurenine pathway enzymes and inflammatory factors in placental tissue from women with and without PE. Methods: Thirty-six placentas (18 PE and 18 controls) were analyzed for expression of kynurenine pathway enzymes indoleamine-2, 3-dioxygenase (IDO1 and 2), tryptophan-2, 3-dioxygenase (TDO), kynurenine-3-mono-oxygenase (KMO) and quinolinate phosphoribosyltransferase (QPRT) as well as interleukin (IL)-1β, IL-6, and serum amyloid A (SAA). Tryptophan and kynurenine content were measured using high-pressure liquid chromatography and quinolinic acid was measured using gas chromatography-mass spectrometry. Conclusions: Tryptophan content was reduced in placentas from women with PE. There was an increased kynurenine/tryptophan ratio in placentas from women with PE but no significant change in downstream metabolites. We confirmed a reduction in IDO1 expression and found a compensatory increase in TDO expression in placentas from women with PE. SAA was reduced in PE placentas compared with controls. Our data show that tryptophan content and the inflammatory mediator SAA are both compromised in placentas from women with PE. Further studies on the role of tryptophan catabolism and mediators of inflammation in sustaining healthy immunobiological pathways in the placenta are warranted.